486 Prognostic value of pet-ct scan on survival outcomes of advanced-staged ovarian cancer patients treated with neoadjuvant chemotherapy: a prospective study. (4th December 2020) - Petousis, Stamatios; Cazeau, Anne-Laure; Crombe, Amandine; Margioula-Siarkou, Chrysoula; Kind, Michel; Croce, Sabrina; Floquet, Anne; Guyon, Frederic
Abstract : Introduction/Background: PET-CT is an imaging examination whose preoperative diagnostic value in advanced-staged ovarian cancer patients remains controversial. Main objective of this study was to answer whether performing early preoperative PET-CT scan in patients undergoing neoadjuvant chemotherapy may discriminate their response and prognosis. Methodology: A prospective observational study was performed between September 2014 and May 2016. There were exclusively included patients diagnosed with advanced-stage ovarian cancer considered as not eligible for primary debulking surgery according to laparoscopy Fagotti score. These patients were treated with four cycles of neoadjuvant chemotherapy with carbotaxole followed by interval debulking and three additional cycles of chemotherapy. PET-CT was performed between the initiation of chemotherapy (T0), first (T1) and fourth cycle of chemotherapy (T4). Follow-up outcomes of patients were also recorded. Primary outcomes were SUV (Standardized Uptake Value), MTV (Metabolic Tumor Volume) and TLG (Tumor Lesion Glycolysis) that were assessed by three different blind physicians each. Total and percentage modifications of these parameters within T0, T1 and T4 were compared between patients with and without recurrence and cancer-related death, while they were also correlated with OS and DFS in a Cox regression analysis. Results: τhere were 10 patients recruited for this study. All patients managed to have complete excision of the disease. SUVmax, MTV and TLG did not present significant interobserver variability within physicians. SUVmax was reduced at 45.9% between T0 and T1 in patients with later cancer-related death vs. only 8.0% in survivors (P=.05), while the relative mean decrease in absolute units was 6.5 vs 1.17 (P=.06). Similarly, TLG between T0 and T1 was reduced at 76.51% vs. 33.7% (P=.04), while mean TLG decrease was 1663.8 vs 653.8 units respectively (P=.06). In contrary, patients not presenting recurrence were characterized by significantly higher TLG reduction between T1 and T4 (95.0% for non-recurrence vs 69.1% for recurrence, P=.04), while TLG mean reduction was 1088 vs. 211 units (P=.11). Furthermore, all mean values of PET-CT parameters presented a higher reduction between T1 and T4 in patients not presenting recurrence. Conclusion: PET-CT examination preoperatively in advanced-staged ovarian cancer patients may be prognostic. Further studies with larger sample size should be performed in order to assess the exact role of PET-CT scan on preoperative triage of advanced-stage ovarian cancer patients. Disclosures: Authors have nothing to disclose.